2019
DOI: 10.1111/1745-9125.12227
|View full text |Cite
|
Sign up to set email alerts
|

School punishment and interpersonal exclusion: Rejection, withdrawal, and separation from friends

Abstract: School suspension is a common form of punishment in the United States that is disproportionately concentrated among racial minority and disadvantaged youth. In labeling theories, the implication is that such stigmatized sanctions may lead to interpersonal exclusion from normative others and to greater involvement with antisocial peers. I test this implication in the context of rural schools by 1) examining the association between suspension and discontinuity in same‐grade friendship ties, focusing on three mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 85 publications
(92 reference statements)
0
44
1
Order By: Relevance
“…As mentioned above, a growing body of literature has demonstrated how exclusionary school discipline (i.e., suspension and expulsion) influences dropping out and delinquent behaviors (Fabelo et al, 2011;Mowen & Brent, 2016;Wolf & Kupchik, 2017), making it especially important that schools consider the potential attrition effects of school punishment. Another recent studyframed using labeling theoryexamined the effects of suspension on peer association and found that school punishment related to greater discontinuity in friendship ties (based on self-reported preferences and peer reports) and increased involvement with substance-using peers (Jacobsen, 2019). This study suggests that there are potential labeling effects of school punishment, whereby suspended students are socially excluded and turn to the company of deviant peers.…”
Section: Discussionmentioning
confidence: 80%
“…As mentioned above, a growing body of literature has demonstrated how exclusionary school discipline (i.e., suspension and expulsion) influences dropping out and delinquent behaviors (Fabelo et al, 2011;Mowen & Brent, 2016;Wolf & Kupchik, 2017), making it especially important that schools consider the potential attrition effects of school punishment. Another recent studyframed using labeling theoryexamined the effects of suspension on peer association and found that school punishment related to greater discontinuity in friendship ties (based on self-reported preferences and peer reports) and increased involvement with substance-using peers (Jacobsen, 2019). This study suggests that there are potential labeling effects of school punishment, whereby suspended students are socially excluded and turn to the company of deviant peers.…”
Section: Discussionmentioning
confidence: 80%
“…Further, effective academic instruction and behaviour support structures protect against the risk of suspension, school failure and early school leaving (Christle et al, 2005). Exclusionary school discipline, however, negatively impacts relationships, school belonging, and academic achievement (Jacobsen, 2020;Lacoe & Steinberg, 2019;Noltemeyer et al, 2015). These effects hold when controlling for factors such as prior achievement, indicating that exclusionary school discipline precipitates rather than mitigates problem behaviours, introducing significant long-term risks, which include poorer educational outcomes than might have already been expected (Rosenbaum, 2020), escalating antisocial behaviours (Hemphill et al, 2006), and early school leaving (Homel et al, 2012;Noltemeyer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…If disassociation from school also increases the likelihood of delinquency, as theories of crime suggest, then school attachment might help explain the relationship between suspensions and crime. Finally, Jacobsen (2020) also interrogated the relationship between suspensions and deviant peer association using labeling theory as a central framework. This study revealed that suspended students were more likely to experience a discontinuity in their friendships and peer rejection, leading to an increased preference for and involvement with antisocial peers.…”
Section: Discussionmentioning
confidence: 99%